One-year follow-up of children hospitalized with COVID-19: a prospective cohort study - Caroline Jacoby Schmidt; Giovana Morin Casassola; Guilherme Hoff Affeldt; Debora Sana Morais; Letícia Krás Borges Alvarenga; Cristina Miller; Bruna Ziegler (Jornal Brasileiro de Pneumologia, 2023)
ABSTRACT Objective: Currently, little is known about the long-term outcomes of COVID-19 in the pediatric population. The aim of this study was to investigate the long-term clinical outcomes of pediatric patients hospitalized with COVID-19. Methods: This was a prospective cohort study involving unvaccinated children and adolescents admitted to a tertiary hospital in southern Brazil with a COVID-19 diagnosis. Data were collected from electronic medical records for one year after the diagnosis. Results: A total of 66 children were included: the median age was 2.9 years; 63.6% were male; and 48.5% were under 2 years of age. Over 70% had at least one comorbidity prior to the COVID-19 diagnosis. During the one-year follow-up period, 59.1% of the children revisited the emergency department, 50% required readmission, and 15.2% died. Younger children with longer hospital stays were found to be at greater risk of readmission. Having cancer and impaired functionality were found to increase the risk of death within one year. Conclusions: Our findings indicate that most children hospitalized with COVID-19 have comorbidities. Younger age at admission and a longer hospital stay seem to be risk factors for readmission. In addition, the presence of cancer and impaired functionality are apparently associated with the poor outcome of death within the first year after the diagnosis of COVID-19.